PENGARUH IT SPENDING TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK SELURUH ASIA TENGGARA PADA TAHUN 2009-2011 - Adrayani, Irene (Modus Journals, 2014)
This study aims to get empirical evidence about the infuence of IT spending on corporate value by testing the efect of IT spending on corporate value by using Tobin’s Q. Te higher the stock price, the higher the company value as well as investors’ assessment. The market price of the company’s stocks refects investors’ assessment of the overall equity held. Of the stock price refects investor can provide an assessment of a company. Tobin’s Q is the ratio of the market value of the company’s assets as measured by the market value of the outstanding stocks and debt (enterprise value) to the replacement cost of the assets of the company. The sampling method is based on purposive sampling method with the purpose to obtain a sample that meets the criteria. Tis study used a sample taken from a telecommunications company listed on the Stock Exchange throughout Southeast Asia during the period of 2009-2011. The hypothesis in this study was tested using simple regression. Based on data analysis, the result that the variable IT spending does not afect the company value.Keywords: accounting information system, Tobin’s Q, IT spending, capital expenditure, company performance